Skeletal muscle in health and disease - Jennifer Morgan; Terence Partridge (The Company of Biologists, 2020)
Skeletal muscle fibres are multinucleated cells that contain postmitotic nuclei (i.e. they are no longer able to divide) and perform muscle contraction. They are formed by fusion of muscle precursor cells, and grow into elongating myofibres by the addition of further precursor cells, called satellite cells, which are also responsible for regeneration following injury. Skeletal muscle regeneration occurs in most muscular dystrophies in response to necrosis of muscle fibres. However, the complex environment within dystrophic skeletal muscle, which includes inflammatory cells, fibroblasts and fibro-adipogenic cells, together with the genetic background of the in vivo model and the muscle being studied, complicates the interpretation of laboratory studies on muscular dystrophies. Many genes are expressed in satellite cells and in other tissues, which makes it difficult to determine the molecular cause of various types of muscular dystrophies. Here, and in the accompanying poster, we discuss our current knowledge of the cellular mechanisms that govern the growth and regeneration of skeletal muscle, and highlight the defects in satellite cell function that give rise to muscular dystrophies.